Comparison of Two Versus Three Bilateral Botulinum Toxin Injections Prior to Abdominal Wall Reconstruction - Timmer, Allard S.; Ibrahim, Faduma; Claessen, Jeroen J. M.; Aehling, Carolin J.; Kemper, Tom C. P. M.; Rutten, Martin V. H.; Boermeester, Marja A. (Journal of Abdominal Wall Surgery, 2023)
Background Intramuscular injection of botulinum toxin A (BTA) induces a temporary muscle paralysis. In patients with a ventral hernia, preoperative injection of BTA in the muscles of the lateral abdominal wall (LAW) leads to thinning and lengthening of these muscles, making fascial closure more likely. In many hernia centres, treatment with BTA prior to abdominal wall reconstruction has therefore become standard care. However, evidence on the optimal BTA strategy is lacking. Methods In this single-centre retrospective study, we analysed a consecutive cohort of ventral hernia patients that underwent bilateral BTA injections prior to abdominal wall reconstruction with available CT before and after BTA. We only included patients that were treated with exactly 600 units of Dysport®, diluted into 120mL of saline, via either two- or three injections on each side into all three LAW muscle layers. The primary outcome was the change in LAW muscle length and thickness, comparing CT measures from before BTA and four to six weeks after the injections. Results We analysed 67 patients; 30 had received two injections bilaterally and 37 had received three injections bilaterally. Baseline data showed no significant differences in LAW muscle thickness or length between groups. In both groups, the median LAW muscle thickness decreased with 0.5 cm (p<0.001). The LAW muscle length increased with 0.9 cm (p=0.001) and 1.2 cm (p<0.001) in the two- and three bilateral injection group, respectively. The BTA-induced changes in LAW thickness and length were not significantly different between both groups (p=0.809 and p=0.654, respectively). Discussion When using the exact same dosage and distribution volume of BTA in patients with a complex abdominal wall defect, two injections bilaterally in the lateral abdominal wall muscles are as effective as three injections bilaterally.